The Relationship Between Physical Activity and Mental Health Among University Students - Dio Aidil fitra; Maidatul Munawarah (Inspire Global Insight Journal, 2026)
Purpose of the study: The transition to university life presents significant psychological challenges for students, including increased stress, anxiety, and depression. Physical activity has been recognized as a potential intervention for improving mental health outcomes, yet comprehensive understanding of this relationship among Indonesian university students remains limited. This study aimed to investigate the relationship between physical activity levels and mental health indicators among university students at Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, examining the potential mediating factors and identifying optimal activity patterns for mental health benefits. Materials and methods: A cross-sectional study was conducted with 420 students (aged 18-25 years) from Sekolah Tinggi Olahraga dan Kesehatan Bina Guna. Physical activity levels were assessed using the International Physical Activity Questionnaire (IPAQ-SF), while mental health was evaluated using the Depression Anxiety Stress Scale-21 (DASS-21) and the World Health Organization Well-Being Index (WHO-5). Data were analyzed using correlation analysis, multiple regression, and structural equation modeling. Results: Students with high physical activity levels demonstrated significantly lower depression (M = 8.2, SD = 4.1) and anxiety scores (M = 7.8, SD = 3.9) compared to low-activity students (depression: M = 14.6, SD = 6.2; anxiety: M = 13.4, SD = 5.8; p < 0.001). A moderate positive correlation was found between physical activity and well-being scores (r = 0.64, p < 0.001). Students engaging in ≥150 minutes of moderate-vigorous physical activity weekly showed 40% better mental health outcomes. Conclusions: Physical activity demonstrates a significant inverse relationship with negative mental health indicators and positive association with psychological well-being among university students. These findings support the implementation of structured physical activity programs as preventive mental health interventions in higher education settings.